Catalytic Asymmetric Allylboration of Indoles and Dihydroisoquinolines with Allylboronic Acids: Stereodivergent Synthesis of up to Three Contiguous Stereocenters. Issue 46 (13th October 2016) - Alam, Rauful; Diner, Colin; Jonker, Sybrand; Eriksson, Lars; Szabó, Kálmán J.
Abstract: The catalytic asymmetric allylboration of cyclic imines with γ, γ‐disubstituted allylboronic acids provides products with adjacent stereocenters in high yield and stereoselectivity. Various electrophiles, including 3, 4‐dihydroisoquinolines and indoles, were prenylated in a fully stereodivergent fashion by switching the E / Z geometry of the allylboronate and/or the enantiomer of the BINOL catalyst. 3‐Methylindole provided products with three adjacent stereocenters with high stereoselectivity in one synthetic operation. Abstract : One, two, three : The catalytic asymmetric allylboration of cyclic imines with γ, γ‐disubstituted allylboronic acids provides products with adjacent stereocenters in high yield and stereoselectivity. 3‐Methylindole, for example, was converted into products with three adjacent stereocenters in one synthetic operation.